Definition of time operation of the valve shutoff system of gasified premises explosion safety - Москвина, Ирина Игоревна (Eastern-European Journal of Enterprise Technologies, 2014)
The results of experimental tests of springs of shutoff valve GSV-1, operating based on a signal, set by the gas protection system to the shutoff solenoid at an abrupt pressure increase in the inlet gas pipeline are presented in the paper. Operation time of the mechanical part of shutoff valves at the pressure increase in the pipeline up to 50.6 kPa (0.5 atm.) ranges from 1,11 to 1,43 s. Operation time at the signal setting from the gas protection system to the shutoff solenoid - from 1,04 to 1,22 s. Statistical distribution functions of shutoff valves operating time do not contradict the Weibull distribution in terms of the Mann-Whitney U test that will allow to calculate the optimal time intervals of the valve operation. Reasonable reliability parameters of the proposed solenoid shutoff valve and its diagnostics terms will ensure explosion protection of gasified premises and the desired safety level for people in them